Complaint Management System Analysis: Online Community Aspiration And Complaint Services - Heriyanto Heriyanto; Melty Oktavianda; Lia Suprihartini (Publik : (Jurnal Ilmu Administrasi), 2022)
The background of this research is the lack of complaints on the application of the National Public Service Complaint Management System - People's Online Aspirations and Complaints Service (SP4N-Lapor) and the slow handling of complaints submitted by the public. This study aims to determine the implementation of the SP4N-Lapor program in Pontianak City. This type of research is qualitative. The results of the study indicate that the implementation of the SP4N-Lapor program has been specifically measured using the Policy Implementation Theory. Based on the standard variables and policy objectives, the implementation of the program is in accordance with the aims. In addition, the variable resources of facilities and infrastructure are sufficient, but human resources are still not optimal. Variable characteristics of implementing agents have been right on target, variable attitudes or tendencies (disposition) of the implementers have carried out their duties well, variables of communication between organizations and activities of implementing communication have been carried out and established and variables of the economic, social and political environment have been running smoothly. To conclide, the overall implementation has been going well and found the inhibiting factor, namely the limited human resources that hinder the implementation of SP4N-LAPOR.